Optimal Island City Capacity: Ternate City Case - Muhammad Zais M. Samiun (AIBPM Publisher, 2022)
Cities that grow on an island have limitations in utilizing space for various activities. The limited space of island activity, population growth, and high urban activity have signaled the need to analyze the optimal capacity of island cities. With the Ternate City case study, this study aims to determine the capacity of island cities economically by analyzing the optimal size of island city residents. The optimal measurement of island cities uses the Alonso-Richardson approach, minimum management cost, net benefit, and long-term profit. The results of the analysis showed that the city of Ternate, with a population density of 1,264 people / km2 per the year 2020, has exceeded the optimum capacity of the size of the city both from the minimum per capita city management fee (658 people/km2) and from the maximum approach of per capita benefits (877 people/km2). While from the long-term maximum per capita profit approach, the city's population is still below the optimum limit (2,054 inhabitants/km2). Thus, strict population control is essential, especially on Ternate island, through the spread of residents and activities directed to islands or sub-districts whose urbanization is still below the optimum point of the city population.